Transformation of Agricultural Land for Urbanisation, Infrastructural Development and Question of Future Food Security: Cases from Parts of Hugli District, West Bengal - Giyasuddin Siddique; Nabanita Mukherjee (Space and Culture, India, 2017)
Developing countries of the world encounter urbanisation and infrastructural development in or around the fertile tracts and the absence of any landuse plan for desired land use change has led to conversion of farmlands, which is detrimental to future food security and environmental quality. Hugli district is traditionally well known as one of the most prosperous agricultural regions of West Bengal but the district is experiencing rapid urban extension and infrastructural development towards productive agricultural land since 1991. This has caused decline in the amount of agricultural production which may be treated as an indicator of increasing threat to the long run sustainable livelihood security of the people of the whole of West Bengal. This article critically explores the transformation of agricultural (farm) land because of growing rate of urbanisation and infrastructural development, which in turn poses the question of threat to food (in) security. Although, this is a growing problem across the universe, this article probes the future food security questions of Hugli district, West Bengal by examining the impact of the highly intertwined indicators of urbanisation and infrastructural development on agricultural (farm) land use and its effect on food security. Regression analysis, Spearman’s Ranking Correlation Coefficient, Remote Sensing technologies, Markov Chain Model, Projection of future population growth and yield rate are employed to understand the depth of the problem. The result not only shows a direct negative correlation between urban extension and agricultural areal contraction but also the supervised classification of satellite imageries shows that there is rapid change of rural land use from 1996-2016. There is no match between future population growth and future yield rate of crops and the Markov Chain Model further predicts that the cropland will decrease from 62.77% to 42.90% and the built up area will increase from 31.86% to 54.63% of the total area from 2016 to 2056.